Analisis Yuridis Efektivitas Penerapan Undang-Undang Nomor 31 Tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 13 Tahun 2006 tentang Perlindungan Saksi dan Korban dalam Proses Pemeriksaan Perkara Pidana di Kota Batam - Cang Elin (Universitas Internasional Batam, 2020)
Witness is a person who sees, hears, and directly experiences the occurrence of a criminal act. The information conveyed by the witness can assist the investigation process to the court to reveal the actual criminal suspect. Meanwhile, victim is a person experiencing the occurrence of a criminal act that causes harm materially or physically. This study uses empirical research methods which in this study the writer used research from primary data.The results of this study are witnesses and victims have priority in their statements during the investigation process of criminal cases both at the investigation stage and the court investigation stage. The implementation of protection as in the Act on Witness and Victim Protection in Batam City has not been fully effective because there are several rights of witnesses and/or victims that cannot be fulfilled by the Police since there are no special authority and special budget to provide protection for witnesses and/or victims in criminal cases in Batam city.